Addressing sick building syndrome and its connection to headache disorders - Valença, Marcelo Moraes; Franco, Otávio Augusto de Oliveira; Peres, Mario Fernando Prieto; Andrade, Juliana Ramos de (Headache Medicine, 2025)
IntroductionSick Building Syndrome (SBS), a term introduced by the World Health Organization in 1983, refers to the occurrence of acute health and comfort issues in individuals occupying specific indoor environments without an identifiable clinical cause. Among the most commonly reported symptoms are headaches, particularly migraines and tension-type headaches, which significantly affect daily functioning and workplace productivity.ReviewThis review examines the primary environmental, chemical, biological, and psychosocial factors contributing to SBS and their influence on the onset and exacerbation of headaches. Poor indoor air quality, inadequate ventilation, and elevated carbon dioxide (CO₂) levels are identified as major physical factors. CO₂ concentrations above 1000 ppm are associated with impaired cognitive function, cerebral vasodilation, and the onset of headaches. Exposure to volatile organic compounds from office materials and cleaning agents, as well as biological contaminants such as mold and dust mites and electromagnetic radiation, is also implicated. In parallel, psychosocial elements such as occupational stress, poor ergonomics, and limited access to natural light exacerbate headache symptoms. The cumulative effect of these stressors contributes not only to physical discomfort but also to decreased performance and increased presenteeism. Preventive measures include improving ventilation systems, implementing green building practices, regulating humidity levels, implementing ergonomic interventions, and promoting mental well-being in the workplace.ConclusionsSBS is a complex occupational health issue strongly associated with headache disorders. Addressing its multifactorial causes through integrated environmental and organizational strategies is essential for enhancing employee health, reducing headache incidence, and improving productivity. Tackling SBS represents both a health imperative and a strategic investment in workplace sustainability.